Removal of methylene blue dye from aqueous solution using alginate grafted polyacrylonitrile beads - Salisu, Ahmed (Scholars Research Library, 2015)
In this study, the removal of methylene blue (MB) dye using alginate graft-polyacrylonitrile beads was investigated. The effects of adsorption parameters such as initial pH, contact time, initial dye concentration and adsorbent dose were studied. The removal efficiency of the beads has been found to be depended on pH. The experimental equilibrium data was successfully fitted to Langmuir isotherm model with the maximum monolayer coverage of 3.51 mg g-1 and adsorption kinetics data has been well fitted by a pseudo-second-order kinetic model. The alginate based beads could be used as low-cost and eco-friendly adsorbent for removal of trace amount of methylene blue in aqueous solution.